Simplifying Expressions

Easy

Medium

Difficult

Q1) 6x +9x =
Q1) 9x + 10y+3x-3y =
Q1) \(3z + 15y-10z+5y \)
Q2) 2x x 9y
Q2) 6x + 4z+8x-3z =
Q2) \(13z + 15y-5z-8y \)
Q3) 6x +4x =
Q3) 3y + 6x+4y+10x =
Q3) \(12abc + 2y-10abc-7y \)
Q4) 7w x 10y
Q4) 5w + 9z+2w-8z =
Q4) \(18z + 9y+4z+9y \)
Q5) 6w x 5x
Q5) 6y + 7x+7y+6x =
Q5) \(11ab + 11y-3ab+5y \)
Q6) 9w x 2x
Q6) 6w + 4y+4w-9y =
Q6) \(9xy^2 + 16y-3xy^2-9y \)
Q7) 9x +4x =
Q7) 6w + 10y+5w-6y =
Q7) \(3ab + 11y-10ab+4y \)
Q8) 2w x 3y
Q8) 4x + 10y+4x+5y =
Q8) \(14z + 20y-6z-8y \)
Q9) 3w x 7y
Q9) 9z + 4w+2z+8w =
Q9) \(13xy^2 + 19y-9xy^2-9y \)
Q10) 8x +3x =
Q10) 5y + 4w+8y-7w =
Q10) \(13xyz + 6y+4xyz+8y \)